Nutrient Balance after Thirteen Years of Organic and Chemical Nutrient Management and Yield Sustainability of Groundnut-Fingermillet Rotation in Rainfed Alfisols of Semi-Arid India - Pharande, V. Rupendra Manideep, R. Prakash Naik, Ch. Srinivasarao, B.K. Ramachandrappa, Sumanta Kundu, B. Venkateswarlu, A.L. (Journal of the Indian Society of Soil Science, 2014)
Higher yields and continuous cropping to meet the ever increasing population of India without optimum supplementation resulted in mining of nutrient reserves in soil. Estimates of the amount of nutrients required to balance inflows and outflows and thus prevent or reduce nutrient depletion are useful indicators for designing soil and fertilizer management strategies to prevent land degradation and increase production. Nutrients balance such as nitrogen (N) and phosphorus (P) are increasingly used as an indicator of the environmental performance of agricultural sector in international and global context. The study focused on nutrient balance of agricultural soil and crop performance in a long-term experiment (1992-2004) on Alfisols of Bengaluru by using organic (farmyard manure, FYM), chemical (NPK) and integrated nutrient management (INM) to measure crop yield and nutrient balance for groundnut (Arachis hypogaea) – fingermillet (Eleusine coracana) crop rotation. The study was conducted to estimate the nutrient use efficiency and soil nutrient balance of five combinations of organic and chemical sources of nutrients. The treatments consisted of control; organic (FYM 10 t ha-1); INM (FYM 10 t ha-1 + 50% NPK; FYM 10 t ha-1 + 100% NPK) and chemical (100% NPK). The 13-year mean yield showed application of FYM was as effective as 100% NPK and FYM 10 t ha-1 + 100% NPK showed higher yield for fingermillet (2.34 t ha-1), and FYM 10 t ha-1 for groundnut (2.08 t ha-1). Practically it is difficult for the farmers to apply 10 t FYM ha-1 every year, therefore, application of available organic amendments at a lower rate in conjunction with chemical fertilizers can maximize the yield. There was a positive slope for yield as well as nutrient uptake for the study period with organic and integrated use of nutrients. There were negative apparent balances for K, secondary and micronutrients in all treatments at variable degree, meaning that these nutrients are being depleted from the soil system. However, positive balances were obtained for N and P. Higher negative nutrient balances were observed for chemical fertilizer treated soils, and significantly higher actual balance was observed in integrated treatments followed by organic, chemical and control treatments. Finally, nutrient build-up index and nutrient depletion index for macronutrients showed significant correlations with sustainable yield index.